Pengaruh Sistem Pengendalian Internal Pemerintah, Budaya Organisasi, Anti-Fraud Awareness Terhadap Pencegahan Fraud - Nadya Wati; R. Septian Armel; Siti Samsiah (Politeknik Raflesia Press, 2025)
The objective of this study is to examine and analyze the influence of the Government Internal Control System, organizational culture, and anti-fraud awareness on fraud prevention in urban village governments (kelurahan) in Bengkalis Regency. The population in this study consists of all urban village employees in Bengkalis Regency, comprising 19 kelurahan. The sampling technique used in this study is purposive sampling. The selected sample includes 4 individuals from each kelurahan: the Head of Kelurahan (Lurah), the Secretary of Kelurahan, the Head of the Economic Business Group (UEK), and the Treasurer of the UEK, resulting in a total sample of 76 respondents. The type of data used is primary data obtained from questionnaires. The data analysis technique employed is multiple linear regression using SPSS version 24. The results show that the Government Internal Control System, organizational culture, and anti-fraud awareness significantly influence fraud prevention.